Strategic human resource management in the era of environmental disruptions - Kim, Sunghoon; Vaiman, Vlad; Sanders, Karin (Human Resource Management, 2022)
AbstractThis article—which serves as an introduction to the special issue of the role of (strategic) human resource management (HRM) in the era of environmental disruptions—summarizes previous research, introduces articles related to this special issue, and provides suggestions for future research in the area. This special issue intends to advance HRM research by putting it in the context of disruptive environments, aiming to deepen our theoretical and empirical knowledge about the role of HRM in these disruptive environments, and provide insights to managers and policymakers who must deal with current as well as future disruptions in extra‐organizational environments. The different sections of this introductory paper are structured from the perspective of an individual (“How can HRM help individual employees cope with environmental disruptions?”), an organization (“How can HRM help organizations be more resilient against environmental disruptions?”), and a community/societal perspective (“How can HRM help the community being affected by environmental disruptions?”). We conclude by proposing several research ideas and practical implications for human resource professionals that would enable them to deal with individual employees, their organization, and the community in times of environmental disruptions.